2018
DOI: 10.5546/aap.2018.eng.316
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative characteristics of combined pharyngoplasty and tonsillectomy versus tonsillectomy in children with obstructive sleep apnea syndrome

Abstract: Tonsillectomy in conjunction with pharyngoplasty reduced the duration of the healing process and blood loss, compared with tonsillectomy alone; however, postoperative complications did not increase. We consider pharyngoplasty in conjunction with tonsillectomy has great potential in the treatment of children with obstructive sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Velopharyngeal insufficiency may occur when the upper airway is structurally modified by excessive manipulation, which affects the position and height of the palate, including the uvula. 24 Genc et al had shown a higher incidence of velopharyngeal insufficiency in the pillar suture group than in the control group. 7 However, our summated results showed no statistical significance in velopharyngeal insufficiency.…”
Section: Discussionmentioning
confidence: 95%
“…Velopharyngeal insufficiency may occur when the upper airway is structurally modified by excessive manipulation, which affects the position and height of the palate, including the uvula. 24 Genc et al had shown a higher incidence of velopharyngeal insufficiency in the pillar suture group than in the control group. 7 However, our summated results showed no statistical significance in velopharyngeal insufficiency.…”
Section: Discussionmentioning
confidence: 95%
“…The study qualities ranged between 4 and 9, that is, overall moderate or high quality (Table 1 ). 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 …”
Section: Resultsmentioning
confidence: 99%
“…29 White pseudomembranes in the non‐suturing group would take longer to slough off. 23 Infection or the sloughing of fibrin clots might expose and erode the small vessels. Therefore, we considered the existence of a suture might protect against secondary hemorrhage caused by blood vessels or mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Shallow anesthesia may induce laryngeal spasms, but the incidence of laryngeal spasms was the same among the three groups observed in this study, which may be related to the fact that there were 46-56 patients in the three groups of samples selected in this study and that intraoperative cold incision had less damage to blood vessels and nerves, light wound bleeding and edema, and lower risk of blood aspiration to the respiratory tract. With the increase in the depth of anesthesia, children might also experience hypoxemia that might induce trauma to children, despite an increase in analgesic effect, which was not conducive to their postoperative rehabilitation (20). Under a certain anesthesia depth index interval, extubation can effectively avoid sudden awakening caused by shallow anesthesia depth (21,22).…”
Section: Discussionmentioning
confidence: 99%